Concurrent engineering: effective deployment strategies - Unny Menon; Michael Graham (Production)
This paper provides a comprehensive insight into current trends and developments in Concurrent Engineering for integrated development of products and processes with the goal of completing the entire cycle in a shorter time, at lower overall cost and with fewer engineering design changes after product release. The evolution and definition of Concurrent Engineering are addressed first, followed by a concise review of the following elements of the concurrent engineering approach to product development: Concept Development: The Front-End Process, identifying Customer Needs and Quality Function Deployment, Establishing Product Specifications, Concept Selection, Product Architecture, Design for Manufacturing, Effective Rapid Prototyping, and The Economics of Product Development. An outline of a computer-based tutorial developed by the authors and other graduate students funded by NASA ( accessible via the world-wide-web ). is provided in this paper. A brief discussion of teamwork for successful concurrent engineering is included, t'ase histories of concurrent engineering implementation at North American and European companies are outlined with references to textbooks authored by Professor Menon and other writers. A comprehensive bibliography on concurrent engineering is included in the paper.